2009
DOI: 10.1093/schbul/sbp152
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Mortality Risk in People With Schizophrenia

Abstract: This study examined effects of cigarette smoking on mortality risk in 1213 persons aged 19-69 years with schizophrenia-related psychotic disorders admitted to State of Maryland Hospitals between 1994 and 2000. Inpatient medical records from 7 hospitals were reviewed to obtain demographic information, diagnosis, medication use, as well as smoking and other substance use. Social Security Death Index data were used to identify deaths in the study group between 1994 and 2004. Death records were reviewed to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 36 publications
(32 reference statements)
4
113
3
4
Order By: Relevance
“…14,16, and 17 ) and is both less expensive and easier to access and use than the National Death Index. 18 The SSDI is less complete for younger and foreignborn people, neither of whom was part of our target study population.…”
Section: Discussionmentioning
confidence: 99%
“…14,16, and 17 ) and is both less expensive and easier to access and use than the National Death Index. 18 The SSDI is less complete for younger and foreignborn people, neither of whom was part of our target study population.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients have a 20% shorter life expectancy; most of it is attributable to smoking [37,38]. For 35-54-year-old patients with schizophrenia, the hazard ratio for mortality for smokers versus non-smokers is 2.0 [39].…”
Section: Impact Of Continued Smokingmentioning
confidence: 99%
“…Smoking reduction yields substantial benefits by reducing the toxic intake from smoking, reducing the relative risk of smoking- Smoking-related medical illness is the one of the primary causes of morbidity and mortality in SMI patients. Smoking-related comorbidities are associated with higher proportions of heavy smoking [4], and the greater the number of cigarettes smoked daily, the higher the risk of smoking-related diseases and mortality [13,15,54]. Therefore, smoking reduction is expected to generate health benefits for these smokers, even if they are not ready to, or cannot, quit smoking in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of nicotine dependence put smokers with SMI at increased risk of smoking-related mortality and morbidity [4,13,14]. A recent study reported that adult smokers with schizophrenia had a 145% higher risk of mortality from smoking-related diseases, such as lung cancer, cardiovascular diseases and chronic obstructive pulmonary disease (COPD), than non-smokers [15].…”
Section: Introductionmentioning
confidence: 99%